KINERJA AKUSTIK DAN TERMAL DINDING BATA GEOPOLYMER CELLULAR LIGHTWEIGHT CONCRETE (GCLC): KINERJA AKUSTIK DAN TERMAL DINDING BATA GEOPOLYMER CELLULAR LIGHTWEIGHT CONCRETE (GCLC) - Yuuwono, Abito Bamban; Rakhmanty, Febrione Putri; Kukuh Kurniawan Dwi Sungkono (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2025)
The rapid growth of the construction industry in Indonesia has led to a surge in cement production, a process that is energy-intensive and releases significant amounts of CO2. To mitigate the environmental impact of cement, geopolymer materials have emerged as a sustainable alternative. Given their role as spatial dividers, walls play a crucial role in a building's thermal and acoustic performance. Effective thermal performance can reduce the energy consumption required for air conditioning, while good acoustic performance enhances occupant comfort. This study compared the thermal and acoustic performance of lightweight concrete bricks (using cement as the primary material) with geopolymer bricks (utilizing fly ash). Two simulated rooms with distinct wall materials were constructed, and their temperature and acoustic properties were simultaneously measured. The thermal testing revealed that geopolymer bricks exhibited superior acoustic performance compared to lightweight bricks. Acoustic testing indicated that both brick types performed well acoustically. However, the acoustic performance of lightweight bricks peaked in hot weather, while geopolymer bricks demonstrated better acoustic performance at lower temperatures.